The Impact of Early Marriage on Women: Dampak Pernikahan Anak Perempuan - Hadina Hadina; Lisda Widianti Longgupa; Rahmawati Rahmawati; Zakiah Radjulaeni (Napande: Jurnal Bidan, 2023)
Child marriage is a marriage performed by youth under the age of 19. There were 27 cases of child marriage in 2019 in Sigi Biromaru District and in 2020 there has been an increase of 46 cases. Purpose This study aims to examine the impact caused by child marriage in Kalukubula Village Method This type of research uses a qualitative phenomenological approach. The population in this study were all women who had child marriages in the village of Kalukubula. Informant collection techniques in this study using Snowball Sampling. Data were collected by in-depth interview techniques using interview guidelines. The informants in this study were 10 informants, 5 main informants, namely women who had child marriages, 4 parents as key informants, and the head of KUA as additional informants. Results obtained are that the impact of child marriage is Psychological Impact, stress due to unpreparedness in managing the household and in taking care of children, Biological Impact, is an impact that occurs on health, economic impact, due to difficulties in finding work due to low educational status, Impact Education is one of the impacts of child marriage due to dropping out of school so that when married it is difficult to find jobs. Conclusion Child marriage in Kalukubula Village has psychological, biological, economic and educational impacts. It is recommended that local government parents prevent child marriage from occurring.